ANALISIS KOMPARATIF KUALITAS PELAYANAN, HARGA DAN CITA RASA TERHADAP KEPUASAN PELANGGAN DI AYAM NELONGSO DAN AYAM BAKAR WONG SOLO - Zulfiyah, Hikmiyatul; Pujianto, Agung; Nasution, Ute Ch (Jurnal Dinamika Administrasi Bisnis, 2019)
This study uses a quantitative method with survey research using a questionnaire as an instrument. The population in this study were all customers who had bought nelongso, chicken and roasted wong solo chicken in surabaya that were at least 17 years old. Data collection techniques using questionnaires that have been tested for validity and reliability the data analysis technique used to answer the hypothesis is the test of independt sample t test.The result of this study indicate that all independent variables, namely service quality, price and taste have differences to the dependent variable of customer satisfaction. Significant value of service quality variables of 0.007 followed by price variables have a value of 0.0001 and then the taste variable has a signifinac value of 0.001 and the last variables dependent customer satisfaction has a significance value of 0.002. all variables have a significance value of <0.05. which means that all independent variables of service quality,price,and taste have defferences in customer satisfaction in nelongso and rosdted chicken wong solo.Keywords: service quality, price,taste,customer satisfaction